Research on Intelligent Speech Guide Robot Control Method Based on Machine Vision. (October 2019) - Wang, Zhengbo; Ma, Xing; Mu, Chunyang
Abstract: Robotic navigation via speech guidance gain potential attention on the field artificial intelligent and it stat-of-art. This paper highlights speech guide for robot toward machine vision were designed. The robot navigation can determine and identify the objects around the blind area. The process of determining the direction and distance of the blind people to consider for deciding and predicating the next step. The information of the sensors is fused together, and a path information suitable for the blind person is transmitted to the user via speech voice broadcast are the key elements for identification part. Moreover, deep learning algorithm are involve for accurate classifiers target into categories, to archive the highest recognition accuracy. The direction and distance are judgment part to adopt include the improvements binocular ranging, angle measurement algorithm with a consideration of errors marge less than 2%. The novelsystem can-authcorrect and, guide blind people to move froward, advance, stop, turn, which greatly compensates for the visual defects of the blind, with respect of constraint of improving the indoor safety of the blind people.